Patient comfort in periapical examination using digital receptors - Gonçalves, Andréa [UNESP]; Wiezel, V. G.; Gonçalves, Marcelo [UNESP]; Hebling, Josimeri [UNESP]; Sannomiya, E. K. (British Inst Radiology, 2009)
Objectives: The aim of this study was to compare digital and conventional radiography with regard to patient comfort during periapical radiographic examination.Methods: 300 patients were submitted to a simulation of a radiographic periapical examination of a dentate region using conventional intraoral radiographic film (Kodak Insight) with and without the use of an RINK film holder, a Schick charge-coupled device (CCD) sensor, a Visualix CCD sensor and a Denoptix phosphor plate. The patients were asked to score how they felt in terms of comfort on a 100 mm visual analogue scale. The Wilcoxon test (alpha = 0.05) was applied to compare the comfort score of different types of imaging receptor from each simulated radiographic region reported by the patients.Results: The median of the comfort data according to the type of imaging receptor was 40 mm for conventional intraoral radiographic film with the use of the film holder, 85 mm for conventional intraoral radiographic film without the film holder, 80 mm for Schick and Visualix receptors, and 90 mm for the Denoptix receptor.Conclusions: Denoptix was the most comfortable imaging receptor, followed in decreasing order by Schick and Visualix, conventional intraoral radiographic film without using the film holder and conventional intraoral radiographic film with a film holder. Dentomaxillofacial Radiology (2009) 38, 484-488. doi: 10.1259/dmfr/82025587
Keywords: radiography, dental, digital; radiography, dental; patient satisfaction; patient acceptance of health care; patient care